The commercialization of biospecimens from Indigenous Peoples: A scoping review of benefit-sharing - Tone-Pah-Hote, Tarlynn; Redvers, Nicole (Frontiers in Medicine, 2022)
Background: There is ongoing and increasing interest in the commercialization of biospecimen-derived products from Indigenous Peoples. Discourse on benefit-sharing specifically in the context of the commercialization of Indigenous Peoples biospecimens are currently lacking. A better understanding of the potential ethical imperatives is in need of exploration on this emerging topic. This review sought to elucidate through categorization the current discourse in the peer-reviewed literature on the commercialization of Indigenous Peoples’ biospecimens from a benefit-sharing perspective. Methods: A scoping review methodology was utilized to perform a search of PubMed, CINAHL, Embase and Google Scholar. A two-stage screening process was used to assess the relevance of any included articles with subsequent manual open coding of articles. Content analysis was applied to identify the main categories and sub-categories within the article data. Results: Thirty-three articles met the inclusion criteria for analysis. Four overarching categories from the included articles were identified regarding the most common discourse on the commercialization of Indigenous Peoples’ biospecimens from a benefit-sharing perspective, including: exploitation through biocolonialism, sovereignty and Indigenous rights, ethical considerations for benefit-sharing, and guidelines and standards concerns. Conclusion: This scoping review highlighted the crucial need to keep Indigenous communities at the center of research projects, ensuring any benefits, advancement, and potential commercial profits are returned to communities through clear and ethical agreements. We encourage all research institutions and institutional ethical review bodies to better clarify the collective needs and interests of Indigenous communities while centering their sovereignty and rights within the research process as it pertains to potential biospecimen product commercialization.